One-step metallization of weft-knitted fabrics for wearable biaxial strain sensors - Tai, Chao-Yi; Lin, Chun-Yu; Liu, Tang-Chun; Jia, Lu-Chiang; Jones, Thomas; Abdolvand, Amin (Scientific reports, 2022)
One-step direct patterning of high definition conductive tracks in textiles is realized through laser direct writing in combination with a silver organometallic ink developed in-house. Photoreduction, nano-crystallization, and sintering are accomplished in one pass under the irradiation of a CW green laser light (λ = 532 nm) at moderate intensities (I ≥ 95 mW/mm 2 ). By tailoring the surface tension and viscosity of the ink, high-definition conductive tracks are formed in weft-knitted polyester-Spandex composite fabrics, well-following the laser’s profile with negligible coffee stain effect. Length resistance as low as 4 Ω/cm is measured and anisotropy of the gauge factor as high as 25 is achieved. The metallized fabric exhibits reversible and hysteresis-free electromechanical responses subject to high strains. Durability assessment qualifies that the as-metallized strain sensors are able to sustain their performance for over 5000 stretch/release cycles, demonstrating its potential applications in biaxial strain sensing and interactive smart textiles.